Investigating the differential efficacy of lecture and demonstration teaching methods in teaching medical-surgical nursing among nursing students - Simeon Oluwole Ogunlowo; Bayo Lawal Ajibade (BMC Nursing)
Abstract Medical-surgical nursing is one of the core courses in general nursing, through which nursing students acquire skills for clinical practice. Medical-surgical nurses work in diverse clinical areas and specialisations to deliver the highest quality care with a view to preserving life, improving health status, and maintaining client health throughout their lifetimes by using an appropriate skill that is better acquired from school through appropriate teaching methods. Hence the need to choose a suitable teaching method to educate the would-be nurses. This study examined the differential efficacy of lecture and demonstration methods for teaching medical-surgical nursing courses in BUTH Ogbomoso with a view to improving the academic performance of nursing students in medical-surgical nursing courses. An experimental research method was used; stratified random sampling was employed to select seventy participants; a pretest was conducted, followed by intervention, and then a post-test. Frequency distribution table, pie chart, bar charts, means, two-tail ANOVA, and t-test were used to analyse the result. Findings revealed that there was a significant difference in the mean score between the two studied groups with a P value of 0.000 < 0.05. It is therefore recommended that medical-surgical nursing educators should not only use the lecture method but employ the demonstration method in teaching medical-surgical nursing. There is a need to equip skill laboratories in the nursing institution for learning.